Trabalho decente docente: um estudo em uma Instituição Federal de Ensino Superior - Maculan, Calusa Grendene (2019)
This study aimed to analyze the working conditions of teachers of a Federal Institution of Higher Education, based on the decent work criteria of the International Labor Organization. To achieve this purpose, the following specific objectives were formulated: a) To analyze the teachers' perception of their responsibilities under the concept of Decent Work defined by the ILO; and b) Identify which decent work criteria established by the ILO are best served by the Federal Institution of Higher Education studied. Thus, a research of descriptive nature was carried out, using a quantitative approach. The data were collected from the application of a closed research instrument that covers issues related to decent work, elaborated by Duffy et al. (2017), as well as questions related to the profile of the respondents. The analysis of the data collected was based on descriptive statistics and exploratory factor analysis, in addition to Cronbach's Alpha. The situation found during the study at IFES demonstrates an adequacy to the general terms of decent work, but has to evolve in search of more ideal conditions. The main points of fragility are free time, destined for rest and leisure. It is hoped that the results of this research can contribute both theoretically, adding to the national literature studies that contemplate the topic of decent work for teachers, as in practice, in the management of educational institutions, which can, by better understanding the theme, outline strategies that help teachers in the search for a job closer to the decent.